Customer Relationship Management from MODENAS as a Buyer's Perspective in a B2B Relationship - Azliza, Abdullah (2009)
The company needs an achievement for business continuously in order to sure the satisfaction of customer every day. This is targeting refer to the group whether individual or organizations. One approach to implement this called Customer Relationship (CRM). The focus in relationship between sellers and buyers is focusing on revenue of benefits to each other and the result is in long-term connection for creating the value. The purpose of this research is to gain the knowledge on how CRM used in B2B situation. In order to gain the purpose, the research question focusing on supplier selection process and benefit from using the development of CRM. The use of research question as a guide, the literature review will look into result in framework concept as followed by collected data. While, in qualitative collected data, the large manufacturer national motorcycle was conduct by interview with high employee and documentation. The observation from this buyer of company overall gives change to look how they look at protruding current supplier by using CRM. The finding in this research shows that through CRM it will bring benefits to both supplier and buyers and not enough also to sure and make lasting the health relationship. This research also shows that when large size global company starting the relation, the complicated process will follow.